1998
DOI: 10.1016/s0378-1097(97)00588-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic organization and function of the aflatoxin B1 biosynthetic genes

Abstract: Aflatoxins are secondary metabolites produced by Aspergillus flavus and Aspergillus parasiticus. Most of the genes involved in the biosynthesis of aflatoxin are contained within a single cluster in the genome of these filamentous fungi. Studies directed toward understanding the molecular biology of aflatoxin biosynthesis have led to a number of important discoveries. A pair of fatty acid synthase genes were identified that are involved uniquely in aflatoxin biosynthesis. Two genes were also characterized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…Molecular genetics con¢rmed these initial reports, as the development of e¤cient DNA transformation systems for both A. £avus and A. parasiticus allowed the elucidation of genes corresponding to the enzyme activities of the AF/ST pathway [10,11,18]. Two gene transfer techniques, gene complementation which involves the restoration of gene function in AF blocked mutants and gene disruption where`knock-out' strains are formed, have been invaluable in assigning the function of the isolated AF/ST genes.…”
Section: Cloning and Molecular Characterisation Of The A£atoxin And Smentioning
confidence: 92%
See 1 more Smart Citation
“…Molecular genetics con¢rmed these initial reports, as the development of e¤cient DNA transformation systems for both A. £avus and A. parasiticus allowed the elucidation of genes corresponding to the enzyme activities of the AF/ST pathway [10,11,18]. Two gene transfer techniques, gene complementation which involves the restoration of gene function in AF blocked mutants and gene disruption where`knock-out' strains are formed, have been invaluable in assigning the function of the isolated AF/ST genes.…”
Section: Cloning and Molecular Characterisation Of The A£atoxin And Smentioning
confidence: 92%
“…£avus transformed with a series of overlapping cosmids containing the AF cluster accumulated averufanin (AVNN) and AVF and was relieved by complementation with the avf1 locus. Sequence analysis of the avf1 locus revealed two genes, a£B and a£W, which encode products with similar amino acid identity to stcB and stcW respectively in A. nidulans but their functions are as yet unknown [18].…”
Section: Cloning and Molecular Characterisation Of The A£atoxin And Smentioning
confidence: 99%
“…Evidence (K. Kusumoto, Y. Nogata and H. Ohta, submitted, also see reference [8]) suggests that several strains of A. oryzae and A. sojae have the entire gene cluster homologous to that of a£atoxin biosynthesis in A. parasiticus, while they do not produce a£atoxin. Klich et al [8] demonstrated that two of three strains of A. sojae express homologs of a£R and fas-1A (a gene encoding fatty acid synthetase for initiation of a£atoxin biosynthesis [3]), but not the other ¢ve homolog genes (norA, nor-1, pksA, ver-1, and omt-1). The reason for this might be that expression of these ¢ve homolog genes requires factors other than a£R in a£atoxin production.…”
Section: Resultsmentioning
confidence: 99%
“…A: The RNA was prepared from the fungal mycelia and was treated with (lanes with odd numbers) or without (even numbers) reverse transcriptase, and used as template for PCR with primers AFLF1 and AFLR1, followed by electrophoresis with 1.5% agarose gel. M, molecular mass marker (100-bp ladder); lanes 1 and 2, A. oryzae IFO 4202 cultivated under a£atoxin-producing condition (the other A. oryzae strains were also cultivated under the same condition); lanes 3 The samples are the same as A, besides CMDF1 and CMDR1 as primers. DNA fragments of 800 bp (size marker), 650 bp (PCR product for the a£R cDNA and DNA) and 270 bp (that for the cmdA cDNA) are indicated with bars.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation